Composição e estrutura da comunidade arbórea e arbustiva em murundus no Pantanal de Poconé, Mato Grosso - Morais, Rodrigo Ferreira [UNESP]; Morais, Fernando Ferreira; Lima, Jose Francisco De (Sociedade de Investigações Florestais, 2014)
Earthmounds fields are flat floodplain, which contain small elevations (morrotes) scattered in the landscape. These earthmounds have different soil and vegetation from the surrounding area, since it does not overflow during the rainy season. It is expected that the size (m²) and volume (m³) of the earthmounds exert influence on the floristic composition and plant community structure. Thus, the aim of this study was analyze the floristic composition and community structure of trees and shrubs in earthmounds in the Pantanal of Poconé, MT, in order to answer two questions: (i) Is there a correlation between the area and volume of the earthmounds with richness and abundance of tree and shrub vegetation? (ii) Is there a correlation between the area and volume of the earthmounds with the basal area of trees and shrubs? Were plots used to delimit the area of earthmounds field to be studied. In each plot, we measured the area and volume of each earthmounds and conducted the floristic and phytosociological survey. We observed that the area and volume influenced the richness, abundance and basal area of the species.

Campos de murundus são áreas planas alagáveis, onde se encontram pequenas elevações (morrotes) espalhadas na paisagem. Esses murundus apresentam solo e vegetação diferente da área circundante, uma vez que não se alagam no período chuvoso. Espera-se que o tamanho (m²) e o volume (m³) dos murundus exerçam influência sobre a composição florística e a estrutura da comunidade vegetal. Assim, o objetivo deste trabalho foi analisar a composição florística e a estrutura da comunidade vegetal arbórea e arbustiva em murundus, no Pantanal de Poconé, MT, com a finalidade de responder a duas perguntas: (i) Existe correlação entre a área e o volume do murundu com a riqueza e abundância da vegetação arbórea e arbustiva? (ii) Existe correlação entre a área e o volume do murundu com a área basal das espécies arbóreas e arbustivas? Foram usadas parcelas para delimitar a área de campo de murundus a ser estudada. Nessas parcelas, formam mensurados a área e volume dos murundus e realizados os levantamentos florístico e fitossociológico. Foi verificado que área e volume influenciaram a riqueza, a abundância e a área basal das espécies.
Composition and structure of tree and shrub community in the earthmound in Pantanal at Poconé, Mato Grosso
Keywords: Biogeografia; Fitossociologia; Campo de inundação; Biogeography; Phytosociology; Flood field